Green Drainage: Theoretical Project for a Flooded Park at IPSEP-PE - Silva, Camila Estefane Ferreira da; Britto, Diogo Caldas de; Silva, Victor Manoel Lins da; Moura, Micaella Raíssa Falcão de (Technical and Scientific Journal Green Cities, 2025)
This work aims to propose a solution for flooding in the IPSEP neighborhood in Recife, Pernambuco, through the creation of a floodable square that will act as a sponge during rainy periods in the area, promoting infiltration and reducing surface runoff. The research adopted a systematic review (SR) on sponge cities and Sustainable Urban Drainage Systems (SUDS) as its theoretical basis. Data collection was conducted using Google Earth Pro and ESIG tools, with the project part developed in AutoCAD. The study aims to contribute to local water management, addressing its vulnerability to floods. Therefore, the proposal includes the creation of a permeable area with a retention system, serving as an applicable and replicable model for urban water management.